Diplomatic Relations between Indonesia-Australia Since Whitlam, Fraser, Until Hawke Era in An Attempt To Establish Political Stability in Southeast Asia - Anzar Abdullah (SCAD Independent, 2017)
Talking about foreign policy relations of a country, it cannot be explained without adapting to the changes that occur in the growing environment or situation of both countries. Adjustments to the environment and the situation, especially the foreign policy are done in order to maintain the physical, economic, politic and social culture of the country in the midst of the real conditions of the situation occurred, like the history of bilateral relations between Indonesia and Australia). This is a study of the history of Australian foreign policy towards Indonesia since Whitlam government in 1972 until Hawke. The goal of the study is to explain how the foreign policy of the Australian Prime Ministers during their reigns. Although in reality in the course of its history, Australian and Indonesian diplomatic relations were full of intrigues, turmoil and conflicts, but it did not severe the relation of the two nations. Eventually, the conclusion of this study explicitly states that Australia and Indonesia still need each other in an attempt to establish political stability, economic and security in Southeast Asia and the Pacific peacefully.